2011
DOI: 10.1159/000323407
|View full text |Cite
|
Sign up to set email alerts
|

Biological Significance of Glutamate Signaling during Digestion of Food through the Gut-Brain Axis

Abstract: Monosodium L-glutamate (MSG) elicits a unique taste termed umami and is widely used as a flavor enhancer in various cuisines. In addition, recent studies suggest the existence of sensors for L-glutamate (Glu) and transduction molecules in the gut mucosa as well as in the oral cavity. The vagal gastric afferent responds specifically to the luminal stimulation of Glu in the stomach and regulates the autonomic reflexes. The intragastric infusion of Glu also activates several brain areas (insular cortex, limbic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 95 publications
(82 reference statements)
2
16
0
Order By: Relevance
“…Ingested MSG stimulates the umami taste receptors on the tongue, leading to depolarization, calcium‐induced transmitter release and activation of taste nerve fibers, and also the glutamate sensors in the stomach and intestine, locally activating the functions of the digestive tract …”
Section: Discussionmentioning
confidence: 99%
“…Ingested MSG stimulates the umami taste receptors on the tongue, leading to depolarization, calcium‐induced transmitter release and activation of taste nerve fibers, and also the glutamate sensors in the stomach and intestine, locally activating the functions of the digestive tract …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it may be that the characteristics of MSG are more strongly associated with protein than are the sensory characteristics of thickness and creaminess previously identified and thus act as a more reliable cue for protein-based satiety. Alternatively, this improved compensation of protein in the MSG+ condition could be related to post-ingestive stimulation of gut glutamate sensors ( 15 , 42 ) which have been related to enhanced satiety in animals ( 43 45 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Effect of glutamate on brain function: Gustatory and anticipatory cephalic stimuli during a meal yield nutritional information and aid efficient food digestion (Uneyama et al, 2008;McCabe and Rolls, 2007;Young and Ajami, 2000;Tomporowski, 2003;Koopmans, 2011;Uematsu et al, 2009;2010;Kitamura et al, 2011). There is evidence that mammals, including humans, can detect the amount of dietary protein and its quality via cephalic relay to initiate proper digestion in the upper gastrointestinal tract.…”
Section: Effects Of Diet On Risk Of Cardiovascular Diseasementioning
confidence: 99%
“…Further evidence showed that abdominal vagal afferents, which were innervated into the stomach and intestine sending information to the brain, were activated by luminal glutamate (Uneyama et al, 2008;McCabe and Rolls, 2007). There is existence of a glutamate signaling system, metabotrophic glutamate receptors in the gastrointestinal tract (Uneyama et al, 2008;McCabe and Rolls, 2007;Kitamura et al, 2011). Luminal glutamate in the stomach and intestine provides the efferent reflection of the abdominal vagus, supporting the modulation of exocrine and endocrine excretion during digestion.…”
Section: Effects Of Diet On Risk Of Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation